Cleaning of Organic Contamination from EUV Optics Surfaces Using Hydrogen-based Plasmas - Skoro, N.; Gogolides, E. (International Conference on Plasma Surface Engineering, 2013)
The efficiency of optics used in extreme ultraviolet (EUV) range suffers from reflectivity degradation due to oxidation and carbon contamination of mirror surfaces. Therefore, an efficient cleaning procedure should be ascertained in order to facilitate applications of EUV lithography tools. Carbon contamination removal from the mirror surface has been reported in Hydrogen plasmas, and laser-induced Hydrogen plasmas in EUV tools. Here, we performed measurements in a helicon-type RF plasma reactor with hydrogen pressures similar to the ones used in laser-induced plasmas in EUV tools. The method of optical actinometry was used to determine hydrogen atom concentration and the degree of dissociation. The results are compared to those obtained by pressure-rise measurements. Preliminary results of plasma etching of thin organic films (PMMA) were also obtained to assess the cleaning efficiency.